Design, synthesis, and insecticidal activity evaluation of piperine derivatives - Chiying Zhang; Qingqiang Tian; Yahui Li; Yahui Li (Frontiers in Chemistry, 2022)
Structural optimization of natural products has become one of the most effective ways to develop novel pesticides. In this study, 30 novel pesticide derivatives containing a linear bisamide were synthesized. Then, their insecticidal activities against P. xylostella were evaluated. Results indicate that different bisamide substitutes show different larvicidal structure–activity relationships. At the same time, 2-trifluoroethyl is the most efficient substituent. The bioactivity results showed that most of the desired compounds exhibited better insecticidal activity against P. xylostella than piperine. Among them, compound D28 resulted in 90% mortality at 1 mg/ml concentration. This study provides a novel protocol for the discovery of new insecticides. The molecular docking results indicated that compound D28 could act on γ-aminobutyric acid receptors.